Annsemimaximal and Coannsemimaximal Modules - I. M.A. Hadi; , H. Y. Khalaf (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
Some authors studied modules with annihilator of every nonzero submodule is prime, primary or maximal. In this paper, we introduce and study annsemimaximal and coannsemimaximal modules, where an R-module M is called annsemimaximal (resp. coannsemimaximal) if annRN (resp. ) is semimaximal ideal of R for each nonzero submodule N of M.